Penggunaan Label Gizi dan Konsumsi Makanan Kemasan pada Anggota Persatuan Diabetisi Indonesia - Palupi, Ika Ratna; Naomi, Novita Dhian; Susilo, Joko (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2017)
Background: The prevalence of non communicable disease-related to diet such as diabetes mellitus and hypertension is increased in Indonesia. One of the causes is increased consumption of unhealthy foods. Nutrition label is projected as a helpful tool to make healthy choice for consumption of packaged foods. Objective of the study is to identify the relationship between the practice of using nutrition label and consumption of packaged food among members of a diabetes community in Yogyakarta. Method: This study was an observational analytic design with cross sectional approach. Subjects of the study were 55 active members of Persatuan Diabetisi Indonesia (Persadia) of Yogakarta Municipality Hospital, obtained by consecutive sampling. Data of practice in nutrition label use was assessed using a validated questionnaire, while consumption of packaged foods was collected using Semi Quantitative Food Frequency Questionnaire (SQFFQ). Chi-square test at significance level of 0.05 was employed for analyzing the data. Results: Chi square test showed insignificant relationship between the use of nutrition label and consumption of packaged foods, as indicated by p value of 0.176 and confidence interval of 0.62-11.39. Moreover, most of the subjects (80%) had high level of packaged foods consumption, particularly for fat and natrium intake. Conclusion: There was no significant relationship between practice of using nutrition label and consumption of packaged foods among members of Persatuan Diabetisi Indonesia of Yogyakarta District Hospital.